Analisis Keunggulan Komparatif dan Kompetitif Udang Beku Pada Pasar Internasional Jepang - Rizki Yuda Musidi; Amanda Putri; Enjelina Damayanti; Ranjani Nuralifah; Raden Ahmad Rasyid Pradava; Rasidin Karo Karo Sitepu; Nur Faizatul Luthfiah (Universitas Veteran Bangun Nusantara, 2024)
This study explores Indonesia's position as one of the main shrimp exporting countries in the world, with a special focus on frozen shrimp exports, where Indonesia is in fourth position globally. This signals significant opportunities for future expansion. The aim of this research is to assess the superiority and competitiveness of Indonesian frozen shrimp in the Japanese market, relative to other exporting countries. This analysis is based on secondary data collected from UN Comtrade over a fourteen year period, from 2011 to 2024, and uses a quantitative descriptive approach. Comparative advantage is calculated using the RCA and ISP methods, while competitive advantage is measured through EPD. The results show that Indonesian frozen shrimp have strong comparative competitiveness, with the highest RCA value reaching 317.32 and ISP indicating the maturity phase. However, in terms of competitive advantage, there is still room for improvement, as EPD places the product in the falling star category. To increase the competitiveness and value of frozen shrimp exports, it is necessary to implement higher quality standards and use geographical indications. In addition, the government must play a key role in developing competitive advantages, through downstreaming, innovative product design, increasing marketing intelligence, and opening trade diplomacy channels with new countries that have the potential to become markets. Shrimp farmers must also be supported by the government to understand domestic consumer market preferences and segmentation, which will help reduce dependence on imports and improve the competitive position of Indonesian frozen shrimp in the Japanese market.